Media, Machines and Might: Reproducing Western Australia’s Violent State of Aboriginal Protection - Kerr, Thor; Cox, Shaphan; Cox, Shaphan (Edinburgh University Press, 2016)
This paper addresses the prevalence of state violence directed at Aboriginal people. It examines how violence has been reproduced in recent years in the space of Western Australia through mutually-reinforcing relations of financial interest, and how the function of private capital accumulation – in state violence against sovereign Aboriginal people – has remained hidden in white sight. This paper argues that state violence is legitimised through a discourse of Aboriginal protection. After outlining how this discourse and violence have operated in Western Australia, the paper provides a substantive narrative challenging the routine reproduction of state violence against Aboriginal bodies through a close reading of public and media texts. These texts relate to state violence against a blockade preventing land-clearing machines from entering Aboriginal country in mid 2011; state violence against the Nyoongar Tent Embassy in early 2012; and, the government's announcement in May 2011 that it would amend the Aboriginal Heritage Act. Through this analysis, lines are drawn between media, machines and might for the purpose of enabling white sight to see private capital accumulation functioning within the reproduction of state violence against Aboriginal people.